Anticoagulation beyond direct thrombin and factor Xa inhibitors: indications for targeting the intrinsic pathway? - van Montfoort, Maurits L.; Meijers, Joost C. M. (Thrombosis and Haemostasis, 2013)
Antithrombotic drugs like vitamin K antagonists and heparin have been the gold standard for the treatment and prevention of thromboembolic disease for many years. Unfortunately, there are several disadvantages of these antithrombotic drugs: they are accompanied by serious bleeding problems, it is necessary to monitor the therapeutic window, and there are various interactions with food and other drugs. This has led to the development of new oral anticoagulants, specifically inhibiting either thrombin or factor Xa. In terms of effectiveness, these drugs are comparable to the currently available anticoagulants; however, they are still associated with issues such as bleeding, reversal of the drug and complicated laboratory monitoring. Vitamin K antagonists, heparin, direct thrombin and factor Xa inhibitors have in common that they target key proteins of the haemostatic system. In an attempt to overcome these difficulties we investigated whether the intrinsic coagulation factors (VIII, IX, XI, XII, prekallikrein and high-molecular-weight kininogen) are superior targets for anticoagulation. We analysed epidemiological data concerning thrombosis and bleeding in patients deficient in one of the intrinsic pathway proteins. Furthermore, we discuss several thrombotic models in intrinsic coagulation factor-deficient animals. The combined results suggest that intrinsic coagulation factors could be suitable targets for anticoagulant drugs.
Keywords: Venous thrombosis; coagulation factors; arterial thrombosis; drug design